Nitrogen‐Doped Carbon Nanosheets with Size‐Defined Mesopores as Highly Efficient Metal‐Free Catalyst for the Oxygen Reduction Reaction1. (23rd January 2014) - Wei, Wei; Liang, Haiwei; Parvez, Khaled; Zhuang, Xiaodong; Feng, Xinliang; Müllen, Klaus
Abstract Nitrogen‐doped carbon nanosheets (NDCN) with size‐defined mesopores are reported as highly efficient metal‐free catalyst for the oxygen reduction reaction (ORR). A uniform and tunable mesoporous structure of NDCN is prepared using a templating approach. Such controlled mesoporous structure in the NDCN exerts an essential influence on the electrocatalytic performance in both alkaline and acidic media for the ORR. The NDCN catalyst with a pore diameter of 22 nm exhibits a more positive ORR onset potential than that of Pt/C (−0.01 V vs. −0.02 V) and a high diffusion‐limited current approaching that of Pt/C (5.45 vs. 5.78 mA cm−2) in alkaline medium. Moreover, the catalyst shows pronounced electrocatalytic activity and long‐term stability towards the ORR under acidic conditions. The unique planar mesoporous shells of the NDCN provide exposed highly electroactive and stable catalytic sites, which boost the electrocatalytic activity of metal‐free NDCN catalyst.